Erratum: Laser-induced electron diffraction of the ultrafast umbrella motion in ammonia (Struct. Dyn. (2021) 8 (014301) DOI: 10.1063/4.0000046) - Belsa, Blanca; Amini, K.; Liu, X.; Sanchez, A.; Steinle, T.; Steinmetzer, J.; Le, A. T.; Moshammer, R.; Pfeifer, T.; Ullrich, J.; Moszynski, R.; Lin, C. D.; et al. (STRUCTURAL DYNAMICS, 2021)
This article was originally published online on 13 January 2021 with an affiliation for J. Ullrich, Physikalisch-Technische Bundesanstalt, Bundesallee 100, 38116 Braunschweig, Germany, omitted. All online versions of the article were corrected on 13 May 2021. All affiliations appear correctly above.
CRIS-Team Scopus Importer:2023-04-20